An exceptionally preserved Eocene shark and the rise of modern predator–prey interactions in the coral reef food web. Issue 1 (December 2016) - Fanti, Federico; Minelli, Daniela; Conte, Gabriele; Miyashita, Tetsuto
Abstract Background Following extreme climatic warming events, Eocene Lagerstätten document aquatic and terrestrial vertebrate faunas surprisingly similar to modern counterparts. This transition in marine systems is best documented in the earliest teleost-dominated coral reef assemblage of Pesciara di Bolca, northern Italy, from near the end of the Eocene Climatic Optimum. Its rich fauna shows similarities with that of the modern Great Barrier Reef in niche exploitation by and morphological disparity among teleost primary consumers. However, such paleoecological understanding has not transcended trophic levels above primary consumers, particularly in carcharhiniform sharks. Results We report an exceptionally preserved fossil school shark (Galeorhinus cuvieri ) from Pesciara di Bolca. In addition to the spectacular preservation of soft tissues, including brain, muscles, and claspers, this male juvenile shark has stomach contents clearly identifiable as a sphyraenid acanthomorph (barracuda). This association provides evidence that a predator–prey relationship betweenGaleorhinus andSphyraena in the modern coral reefs has roots in the Eocene. A growth curve of the living species ofGaleorhinus fitted toG. cuvieri suggests that all specimens ofG. cuvieri from the lagoonal deposits of Bolca represent sexually and somatically immature juveniles. Conclusion The modern trophic association between higher-degree consumers (Galeorhinus andSphyraena ) has a counterpart in the Eocene Bolca, just as Bolca and the Great Barrier Reef show parallels among teleost primary consumers. Given the age of Bolca, trophic networks among consumers observed in modern coral reefs arose by the exit from the Climatic Optimum. The biased representation of juveniles suggests that the Bolca Lagerstätte served as a nursery habitat forG. cuvieri . Ultraviolet photography may be useful in probing for exceptional soft tissue preservation before common acid preparation methods.